The Effect of Using Quizizz Learning Media to Improve Student Learning Outcomes in Science in Grade V SDN 2 Sindue Tobata - Zain Rahmat Mudzakir; Sinta Satria Dewi Pendit; Sisriawan Lapasere; Abdul Rahman; Putriwanti Putriwanti (Journal of Educational Sciences, 2026)
The integration of digital learning media has become an important strategy for improving student engagement and learning outcomes in elementary education. However, the use of game-based learning platforms such as Quizizz remains limited in elementary science classrooms. This study aimed to examine the effect of Quizizz learning media on the science learning outcomes of fifth-grade students at SDN 2 Sindue Tobata. A quantitative pre-experimental approach using a One Group Pretest–Posttest Design was employed. The participants consisted of 20 fifth-grade students selected through saturated sampling. Data were collected using validated achievement tests and analyzed through descriptive statistics, the Shapiro–Wilk normality test, the Paired Sample t-test, and the normalized gain (N-Gain) test. The findings indicate that Quizizz significantly improved students' science learning outcomes while increasing their motivation, participation, and engagement during classroom activities. The learning improvement reached a moderate level of effectiveness, demonstrating that Quizizz is an effective digital learning medium. This study provides empirical evidence supporting the integration of game-based learning media to promote student-centered science learning in elementary schools.